Assessment of success of financial information system in educational, health, and medical centers affiliated to Isfahan University of Medical Sciences - Sakineh Saghaeiannejad-Isfahani; Nafiseh Salimian-Rizi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Financial information system is one of the subsystems in management information system that is very important in health institutions. The use of financial information system creating effective and efficient information flow will greatly assist the management in decision-making, so that it can achieve institutional goals easier. This study is endeavored to assess the success of financial information system in Isfahan University of Medical Sciences. MATERIALS AND METHODS: This descriptive-correlational study was performed on the research population consisting of financial information system users in educational, health, and medical centers affiliated to Isfahan University of Medical Sciences during 2018 that were studied by the census method (n = 108) because of a small number of these users. The data were collected using a questionnaire. The content validity of questionnaire was confirmed by pooling the ideas of five academic members of the health information management and two financial information system users. The reliability of questionnaire was also estimated by Cronbach's alpha. Then, the AMOS software was used to analyze the gathered data. RESULTS: The result shows that system quality was positively correlated to the use and user satisfaction whereas use and user satisfaction was positively correlated to net benefit (P < 0.05). Furthermore, the information quality was positively correlated to the user satisfaction (P < 0.05). CONCLUSIONS: As per the finding of this study, to improve user's intention to use the financial information system and their satisfaction toward the system, managers need to develop useful, easy-to-understand, easy-to-learn, and easy-to-use information systems.